The allocation of entrepreneurial talent and destructive entrepreneurship - Mark Sanders; Utz Weitzel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Entrepreneurship is generally regarded as a force of change, innovation, and development in modern economies. Entrepreneurs bring new and better products to markets, restore allocative efficiency through arbitrage and reinvest their profits. However, it has been argued that the same energy and talent can also be allocated to unproductive ends and reduce total welfare. In this paper we present a model that analyzes the allocation of a given entrepreneurial talent over destructive and productive activities. We show that in this model two stable equilibria can emerge. As Baumol (1990) hypothesized, institutions determine the payoffs to both types of entrepreneurial activity and hence drive this allocation. But we also show that the distribution of initial wealth and entrepreneurial talent play a decisive role. This analysis provides a different perspective on the importance of high quality institutions in developing countries and sheds light on the situation in conflict and post-conflict countries, where both informal and formal institutions arguably have broken down. Under such circumstances, our analysis shows that microcredits can support the transition to a productive equilibrium, because they help to overcome credit constraints without creating incentives for destructive entrepreneurship.
Keywords: D23; J24; O12; O17; 330; destructive entrepreneurship; allocation of talent; development; institutions